Alcohol consumption and the risk of tuberculosis: a systematic review and Meta-analysis - Simou, Evangelia; Britton, John; Leonardi-Bee, Jo (International Union Against Tuberculosis and Lung Disease, 2018)
OBJECTIVE: To perform a systematic review and meta-analysis of the association between alcohol consumption and tuberculosis risk. METHODS: Medline, EMBASE and Web of Science were searched for observational studies from 2005 to April 2018. Reference lists of included studies were screened. RESULTS: Forty nine studies were included. Compared to people with low or no alcohol intake, the risk of tuberculosis in people with high or any alcohol consumption was increased by a relative odds of 1.90 (95% CI: 1.-2.23). Substantial levels of heterogeneity were seen (I2=82%), but there was no evidence of publication bias (P=0.). Sensitivity analysis restricted to studies using no alcohol drinking as a reference group found a slightly lower but still increased risk (Odds Ratio= 1.59, 95%CI: 1.38-1.84). Subgroup analyses found no significant differences in relation to study design and quality, geographic location, publication year, and adjustment for confounders. A pooled analysis of a further four studies reporting hazard ratios, found nearly a tripling increase in risk of TB in relation to alcohol consumption during follow-up (HR=2.81, 95%CI: 2.12-3.74). An exposure-response analysis showed that for every 10-20 grams daily alcohol intake, there was 12% increase in TB risk. CONCLUSION: Alcohol consumption is an important risk factor for the development of TB.